2023
DOI: 10.1021/acs.jafc.2c08175
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferases Mediate In Vitro and In Vivo Inactivation of Genipin: Implications for an Underlying Detoxification Mechanism

Abstract: Genipin (GP), the reactive metabolite of geniposide (GE), is responsible for GE-induced hepatotoxicity. As a potential detoxification pathway, the inactivation of GP by glutathione S-transferases (GSTs) has not yet been characterized. In this study, the thiol-GSH conjugates of GP, M532-1 and M532-2 were first identified and the catalytic activities of GSTs were investigated both in vitro and in vivo. GSTA1-1 and GSTA4-4 showed high activity in the formation of both thiol-GSH conjugates, whereas GSTA4-4 specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Notably, the previously reported GP-N-GSH conjugate, M496, 5 was also detected in our in vitro studies 34 (Figure S1). As previously reported, M496 formation resulted from the direct conjugation of the primary amino group of GSH to GP, representing the nonenzymatic amino reactivity of GP.…”
Section: Gsh Conjugation Analysis Insupporting
confidence: 86%
See 2 more Smart Citations
“…Notably, the previously reported GP-N-GSH conjugate, M496, 5 was also detected in our in vitro studies 34 (Figure S1). As previously reported, M496 formation resulted from the direct conjugation of the primary amino group of GSH to GP, representing the nonenzymatic amino reactivity of GP.…”
Section: Gsh Conjugation Analysis Insupporting
confidence: 86%
“…Although the absolute concentrations of M496 and M530 in vitro and in vivo can only be compared via quantification using synthetic standards, rough comparison based on peak height make it clear that M530 formation is more prevalent in vivo and M496 is more abundant in vitro. M496 is likely produced via the ring opening of GP from a dialdehyde intermediate and subsequent conjugation to the amino residue of GSH . A previous in vivo study found high levels of GP–amino acid conjugates that likely compete with M496 formation .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, the long-lasting antibacterial ability can be achieved by the thermal-controlled release of curcumin. 24,52,53 As shown in Figure 4d, all the films doped with curcumin showed a sustained release phenomenon. The final release curcumin concentrations order of those films was CS/Cur > CCF 0.05 > CCF 0.1 > CCF 0.15 > CCF 0.2 , and the release rate constant (k) of Cur-based films decreased with the increase of doped Fe-MoO x (SI, Figure S13 and Table S1), which indicated that the doping Fe-MoO x could prolong the release time of curcumin, achieving long-lasting antibacterial effect.…”
Section: Photothermal Effect and Thermal-responsive Release Propertiesmentioning
confidence: 82%
“…All other chemicals were offered by Sigma-Aldrich, if not otherwise indicated. Recombinant human GSTP was prepared in our laboratory as described previously [ 29 ].…”
Section: Methodsmentioning
confidence: 99%